Hürthle cell tumors of the thyroid - Perrone, Luis; Estrugo, Roberto; Iraola, Maria; Botta, Fernando; Doassans, Carlos; Maggiolo, José (Cirugía del Uruguay, 1986)
19 thyroidectomies were perf,rmed and eight tumors to Hürthle cells were found, Upon a brief review ot function of Hürthle cells, authors onclude that there is good correlation between the biological behaviour of tumors and the anatomopathological findings. In accordance wilh definite and concrete histology, precise patterns for treatment were established. The follow up is fully consistent with the definitive pathological anatomy of each case in particular.